Pengaruh Fraksi Volume Pasir Terhadap Kekuatan Bending, Densitas Dan Porositas Keramik Berbahan Dasar Tanah Liat - Bachtiar, Iyas Muzalif; Sudarsono, Sudarsono; Kadir, Abd . (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2019)
The purpose of this study was to determine the effect of adding clay-based ceramic material sand to physical strength using bending, density, and porosity testing methods. In this study using clay and sand with a volume fraction of clay: sand ie 90:10 %, 80:20 %, 70:30 %, 60: 40 % and 50:50 % printed using mold rectangular size 50 mm long, 8 mm wide and 7 mm thick, then the compaction process is carried out with a pressure of 175 kgf/cm2 or 2500 psi, then the sintering process is carried out at a temperature of 800 OC for 1 hour. The tests carried out are density, porosity and bending tests. The results showed that the density value of the volume fraction of 80:20 % obtained the highest average density value of 0.513 gr/cm³, and the volume fraction of 50:50 % obtained the lowest average density value of 0.458 gr/cm³. In porosity testing with a volume fraction of 50: 50 %, the highest porosity value was 67.619 %, and the volume fraction of 80:20 % obtained the lowest porosity value of 44.381 %. And for bending testing, the effect of volume fraction on bending strength obtained the highest bending strength value of 0.516 N/mm² for the volume fraction of 80: 20 % and the lowest bending strength value obtained with a value of 0.075 N/mm² for 50: 50 % volume fraction.Keywords: Sintering, density, porosity, bending, ceramic